2019
DOI: 10.3390/molecules24020312
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical Heterocyclic Cage Skeleton: Synthesis, Urease Inhibition Activity, Kinetic Mechanistic Insight, and Molecular Docking Analyses

Abstract: The present study focuses on the design and synthesis of a cage-like organic skeleton containing two triazole rings jointed via imine linkage. These molecules can act as urease inhibitors. The in-vitro urease inhibition screening results showed that the combination of the two triazole skeleton in the cage-like morphology exhibited comparable urease inhibition activity to that of the reference thiourea while the metallic complexation, especially with copper, nickel, and palladium, showed excellent activity resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
4
14
0
Order By: Relevance
“…In the literature, it is reported that enzymes such as urease and HRP are involved in the metabolism of HU. , Therefore, in the present study, we evaluated the effects of rutin and gallic acid on urease and HRP activity (Figure and Figure ). Thiourea was found to have an IC 50 of 30 μM against urease activity, corroborating a previous study, which also reported similar IC 50 . Rutin and gallic acid demonstrated IC 50 values of 780 and 635 μM, respectively, toward inhibition of urease activity.…”
Section: Resultssupporting
confidence: 88%
“…In the literature, it is reported that enzymes such as urease and HRP are involved in the metabolism of HU. , Therefore, in the present study, we evaluated the effects of rutin and gallic acid on urease and HRP activity (Figure and Figure ). Thiourea was found to have an IC 50 of 30 μM against urease activity, corroborating a previous study, which also reported similar IC 50 . Rutin and gallic acid demonstrated IC 50 values of 780 and 635 μM, respectively, toward inhibition of urease activity.…”
Section: Resultssupporting
confidence: 88%
“…Compound 6238-0047 could interact with Cys318 to interfere with the normal function of the active site flap. All these binding modes showed that compound 6238-0047 could not only bind and interact with residues in the active site pocket but also with the flap outside the active side and these binding behaviors often result in a mixed type inhibitor in the previous report [ 28 , 29 , 30 ] and the kinetic study of compound 6238-0047 confirmed that it was a mixed type inhibitor.…”
Section: Discussionmentioning
confidence: 56%
“…The Protein Data Bank (PDB) was used to retrieve the structure of the jack bean urease enzyme PDBID 4H9M [ 27 ]. The University of California, San Francisco (UCSF) Chimera 1.10.1 tool was used to save the crystal structure of the enzyme in its stable conformation [ 28 ].…”
Section: Methodsmentioning
confidence: 99%